Pharmacogenomics in the Management of Pulmonary Arterial Hypertension: Current Perspectives - Coons JC; Empey PE (Dove Medical Press, 2023)
James C Coons,1,2 Philip E Empey1 1Department of Pharmacy and Therapeutics, University of Pittsburgh School of Pharmacy, Pittsburgh, PA, USA; 2Department of Pharmacy, UPMC Presbyterian-Shadyside Hospital, Pittsburgh, PA, USACorrespondence: James C Coons, Email jccoons@pitt.eduAbstract: Pulmonary arterial hypertension (PAH) is a rare disease with heterogeneous causes that can lead to right ventricular (RV) failure and death if left untreated. There are currently 10 medications representative of five unique pharmacologic classes that are approved for treatment. These have led to significant improvements in overall clinical outcome. However, substantial variability in dosing requirements and treatment response is evident, leading to suboptimal outcome for many patients. Furthermore, dosing is empiric and iterative and can lead to delays in meeting treatment goals and burdensome adverse effects. Pharmacogenomic (PGx) associations have been reported with certain PAH medications, such as treprostinil and bosentan, and can explain some of the variability in response. Relevant genes associated with treprostinil include CYP2C8, CYP2C9, CAMK2D, and PFAS. CYP2C8 and CYP2C9 are the genes encoding the major metabolizing liver enzymes for treprostinil, and reduced function variants (*2, *3) with CYP2C9 were associated with lower treatment persistence. Additionally, a higher CYP2C9 activity score was associated with a significantly less risk of treatment discontinuation. Other genes of interest that have been explored with treprostinil include CAMK2D, which is associated with right ventricular dysfunction and significantly higher dose requirements. Similarly, PFAS is associated with lower concentrations of cyclic adenosine monophosphate and significantly higher dose requirements. Genes of interest with the endothelin receptor antagonist (ERA) class include GNG2 and CYP2C9. A genetic variant in GNG2 (rs11157866) was linked to a significantly increased rate of clinical improvement with ERAs. The *2 variant with CYP2C9 (encoding for the major metabolizing enzyme for bosentan) was significantly associated with a higher risk for elevations in hepatic aminotransferases and liver injury. In summary, this article reviews the relevant pharmacogenes that have been associated to date with dosing and outcome among patients who received PAH medications.Keywords: pulmonary hypertension, pulmonary arterial hypertension, pharmacogenomics